Turning platform workers into owners - Gonza, Tej (Teorija in praksa, 2022)
Platform work is often characterised by economic insecurity, dehumanising control procedures, isolation, deepening racial, economic and gender inequalities, and other socio-economic problems. There are lively debates underway concerned with how to regulate or limit the negative effects of platform capitalism. This article reviews two of the most common calls for action – regulation and platform co-operatives. We argue that there is also an unexplored, complementary option, which uses the network effects of platforms to provide greater benefits for platform workers. To understand this alternative, we introduce the American Employee Stock Ownership Plan (ESOP) mechanism for employee buyouts, redefine the model according to the main cooperative values, and apply it to the platform economy. We conclude that there is a third option is available to governments and municipalities, namely to require an Employee Stock Ownership Plan (ESOP) in the local subsidiary of the platform company